Consequences of school closures due to COVID-19 in DRC, Nigeria, Senegal, and Uganda. - Rawlance Ndejjo; Andrew K Tusubiira; Suzanne N Kiwanuka; Marc Bosonkie; Eniola A Bamgboye; Issakha Diallo; Steven N Kabwama; Landry Egbende; Rotimi F Afolabi; Mamadou Makhtar Mbacké Leye; Noel Namuhani; Yves Kashiya; et al. (Public Library of Science (PLoS), 2023)
In 2020 and 2021, Governments across the globe instituted school closures to reduce social interaction and interrupt COVID-19 transmission. We examined the consequences of school closures due to COVID-19 across four sub-Saharan African countries: the Democratic Republic of Congo (DRC), Nigeria, Senegal, and Uganda. We conducted a qualitative study among key informants including policymakers, school heads, students, parents, civil society representatives, and local leaders. The assessment of the consequences of school closures was informed by the Diffusion of Innovations theory which informed the interview guide and analysis. Interview transcripts were thematically analysed. Across the four countries, schools were totally closed for 120 weeks and partially closed for 48 weeks. School closures led to: i) Desirable and anticipated consequences: enhanced adoption of online platforms and mass media for learning and increased involvement of parents in their children's education. ii) Desirable and unanticipated consequences: improvement in information, communication, and technology (ICT) infrastructure in schools, development and improvement of computer skills, and created an opportunity to take leave from hectic schedules. iii) Undesirable anticipated consequences: inadequate education continuity among students, an adjustment in academic schedules and programmes, and disrupted student progress and grades. iv) Undesirable unanticipated: increase in sexual violence including engaging in transactional sex, a rise in teenage pregnancy, and school dropouts, demotivation of teachers due to reduced incomes, and reduced school revenues. v) Neutral consequences: engagement in revenue-generating activities, increased access to phones and computers among learners, and promoted less structured learning. The consequences of school closures for COVID-19 control were largely negative with the potential for both short-term and far-reaching longer-term consequences. In future pandemics, careful consideration of the type and duration of education closure measures and examination of their potential consequences in the short and long term is important before deploying them.